Systems vaccinology identifies immunological correlates of SARS-CoV-2 vaccine response in solid organ transplant recipients - Nicolas Gemander; Julika Neumann; Rafael Veiga; Isabelle Etienne; Teresa Prezzemolo; Delphine Kemlin; Pieter Pannus; Stéphanie Depickère; Véronique Olislagers; Inès Vu Duc; Alexandra Waegemans; Margaux Gerbaux; et al. (npj Vaccines)
Abstract Solid-organ transplant (SOT) recipients are at enhanced risk of infection and to poorly respond to vaccination due to comorbidities and immunosuppression. We performed a systems vaccinology study in 59 kidney and 31 lung transplant recipients who received 3 doses of COVID-19 mRNA BNT162b2 vaccine. We were able to characterize a baseline configuration associated with an effective humoral response to 3 doses, characterized by an innate and activated B cell profile, whereas a T cell signature was associated with a poorer response. We observed a distinct configuration associated with a detectable humoral response to 2 doses, partly mediated by double negative B cell subsets. These results suggest that, despite their immunosuppression, some SOT recipients can induce an effective humoral response to 3 doses of vaccine supported by a baseline configuration close to the healthy phenotype. Baseline immune phenotyping may help identify SOT recipients at the greatest risk of a poor vaccine response.